2020
DOI: 10.3389/fpsyg.2020.564158
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Anxiety Symptoms and Self-Regulation Capacity Are Associated With the Unpredictability of Maternal Sensory Signals in Caregiving Behavior

Abstract: The unpredictability of maternal sensory signals in caregiving behavior has been recently found to be linked with infant neurodevelopment. The research area is new, and very little is yet known, how maternal anxiety and depressive symptoms and specific parental characteristics relate to the unpredictable maternal care. The aims of the current study were to explore how pre- and postnatal maternal anxiety and depressive symptoms and self-regulation capacity associate with the unpredictability of maternal sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…A subsequent analysis showed that maternal baseline RSA and effortful control buffered the link between mothers’ exposure to chronic family stressors and maternal negative emotionality directed toward the child and others (Deater-Deckard et al, 2016). A similar pattern was observed in a more recent study of maternal effortful control facing parenting stressors with infants (not including child EXT; Holmberg et al, 2020), which provides further evidence that maternal effortful control, executive function, and resting RSA may play a key buffering role.…”
Section: Bidirectional Links Between Child Ext and Hpsupporting
confidence: 82%
“…A subsequent analysis showed that maternal baseline RSA and effortful control buffered the link between mothers’ exposure to chronic family stressors and maternal negative emotionality directed toward the child and others (Deater-Deckard et al, 2016). A similar pattern was observed in a more recent study of maternal effortful control facing parenting stressors with infants (not including child EXT; Holmberg et al, 2020), which provides further evidence that maternal effortful control, executive function, and resting RSA may play a key buffering role.…”
Section: Bidirectional Links Between Child Ext and Hpsupporting
confidence: 82%
“…There is still little understanding of the maternal risk factors related to the high unpredictability of maternal sensory signals. However, previous research has shown that cumulative risk factors such as low maternal self-regulation together with high anxiety symptoms are associated with high unpredictability of maternal sensory signals [ 54 ], opening up one possible avenue for identifying mothers at risk in the clinical context. Moreover, the Questionnaire of Unpredictability in Childhood (QUICK) [ 12 ] was recently developed and validated to assess unpredictable parenting and home environments before the age of 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…This is important as insensitive parental behaviour plays a causal role in shaping insecure child attachment (Bakermans‐Kranenburg et al., 2003 ). In addition, when compared to ‘healthy’ adults and their infant partners, anxious parents exhibit more frequent parental expressions (e.g., infant‐directed speech and positive facial expressions; Murray et al., 2008 ; Granat et al., 2017 ), higher unpredictability (i.e., inconsistency in the order of parental sensory signals; Holmberg et al., 2020 ), increased intrusive behaviour (overcontrolling behaviour that restricts child autonomy; Hakanen et al., 2019 ), and highly synchronous parent‐infant behaviour (Beebe et al., 2011 ; Granat et al., 2017 ). Anxious parents also show higher physiological synchrony with their infants, driven by higher reactivity to small‐scale fluctuations in infant arousal (Smith et al., 2021 ); and anxious caregivers are more likely to vocalise in clusters (i.e., aperiodic ‘bursts’ followed by lulls of inactivity; Abney et al., 2018 ) to their child at times when their own physiological arousal is elevated (Smith et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%